EXPERENTIAL PROCESS IN THE STUDENTS’ WRITING AT ENGLISH LITERATURE OF UMN AL-WASHLIYAH - SOPHA, DIANA (Linguistik : Jurnal Bahasa dan Sastra, 2024)
This research is a study in Systemic Functional Linguistics (SFL) concentrated in Experential Process. It is analyzed in the students’ poetry writing at English Literature of Universitas Muslim Nusantara Al-Washliyah in the academic year of 2020/2021. By applying descriptive qualitative method, this research finds out that all of the six types of processes are realized in the students’ poetry writing. First, the students use Material Process dominantly describing actions of the actor. Secondly, another process they use is Relational Process relating a unit of language to another unit. Third, Mental Process involving senses, cognition, emotion, and perception. Fourth, in the low frequency, they used Existential process showing the existence of an entity. Fifth, Verbal process involves information of saying, asking or telling and sixth, Behavioural process is used to express humans’ behaviours.